Smell Preservation following Unilateral Endoscopic Transnasal Approach to Resection of Olfactory Groove Meningioma: A Multi-institutional Experience - Orgain, Carolyn A.; Kuan, Edward C.; Alvarado, Raquel; Adappa, Nithin D.; Jonker, Benjamin P.; Lee, John Y. K.; Palmer, James N.; Winder, Mark; Harvey, Richard J. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Introduction Olfactory groove meningiomas (OGMs) are often associated with loss of smell following resection. Loss of smell has a measurable impact on quality of life. Smell preservation has been previously described in open approaches for early stage or unilateral OGMs. Evidence of smell preservation in endoscopic approaches is lacking.Design A multi-institutional retrospective review was performed on consecutive patients who underwent unilateral endoscopic endonasal resection of OGM. A gross total resection was achieved with preservation of the contralateral olfactory cleft and bulb. Olfactory function was assessed with a six-point olfactory symptom score and the Sniffin' Sticks 12-item smell identification test (SS-12). Contralateral olfactory bulb volume was measured on postoperative magnetic resonance imaging.Results Four patients (age 42.0 ± 7.5, 75% female) were assessed. Olfactory function was assessed at 21.8 ± 5.6 months following surgery. All patients reported some degree of smell preservation (75% described a slight/mild impairment in smell or better). Olfactory identification was preserved with an SS-12 score of 9 ± 1.4 (anosmia defined as ≤6). The olfactory bulb volume was calculated to be 47.4 ± 15.9 mm3 (normal >40 mm3).Conclusion Smell preservation is possible following unilateral endoscopic endonasal resection of carefully selected OGM.
Keywords: endoscopic; skull base; surgery; olfactory groove meningioma; smell; smell preservation